Down-Regulation of Renal Klotho Expression by Shiga Toxin 2 - Martina Feger; Sobuj Mia; Tatsiana Pakladok; Jan P. Nicolay; Ioana Alesutan; Stefan W. Schneider; Jakob Voelkl; Florian Lang (Karger Publishers, 2014)
Background/Aims: Shiga toxin 2 may trigger classical hemolytic uremic syndrome (HUS) eventually leading to renal failure. Klotho, a transmembrane protein, protease and hormone mainly expressed in kidney is involved in the regulation of renal phosphate excretion and also retains renal protective effects. Renal failure is associated with renal depletion of klotho. The present study explored the influence of Shiga toxin 2 on renal klotho expression. Methods: Mice were injected with either solvent or Shiga toxin 2 and urinary flow rate and phosphate excretion were determined in metabolic cages. Renal transcript levels were measured by quantitative RT-PCR and renal protein abundance by Western blotting. Plasma concentrations of 1,25(OH)2D3 and FGF23 were determined by ELISA and plasma phosphate and urea concentrations by photometry. Results: Shiga toxin 2 treatment was followed by increase of plasma urea concentration, urinary flow rate and renal phosphate excretion but not of plasma phosphate concentration. Shiga toxin 2 treatment strongly decreased klotho mRNA expression and klotho protein abundance in renal tissue. Shiga toxin 2 treatment further increased tumor necrosis factor (TnfE) mRNA levels, as well as protein abundance of phosphorylated p38 MAPK in renal tissue. The treatment significantly increased renal Cyp27b1 and decreased renal Cyp24a1 mRNA levels without significantly altering plasma 1,25(OH)2D3 levels. Shiga toxin 2 treatment was further followed by increase of plasma FGF23 concentrations. Conclusion: Shiga toxin 2 treatment stimulated TnfE transcription, down-regulated renal klotho expression and increased FGF23 formation, effects presumably contributing to renal tissue injury. i 2015 S. Karger AG, Basel